Coupled anatexis and extreme differentiation are the keys for producing giant lithium-rich pegmatites - Hai-Zhen Wei; Martin R. Palmer; Zhiqin Xu; Wenbin Zhu; Xi-Sheng Xu; Anthony Williams-Jones; Bi-Hai Zheng; Jian-Guo Gao; Qin Wang; Jing Ma; Ke Yang; Hefeng Lin; et al. (Proceedings of the National Academy of Sciences, 2026)
Despite the economic importance of lithium, there is considerable disagreement over the processes that concentrate it and other rare metals in pegmatite-type lithium deposits. Two main processes have been invoked, namely extreme differentiation of a peraluminous granitic magma and direct anatexis of a sedimentary protolith. We use geochemical modeling to quantify lithium enrichment via these two processes from a study of the Jiajika lithium pegmatite field, one of the largest of its type in the world. Based on a lithium–silicon–boron–barium (Li-Si-B-Ba) isotope study involving systematic sampling along 4,211-m of core from two deep boreholes and from the regional zonation of pegmatites at outcrops, we propose a three-stage model for the formation of the pegmatite field: i) generation of a rare metal-rich melt by deep anatexis, involving ~5% partial melting of metapelitic rocks in the presence of 10 to 30% metamorphic fluid; ii) gradual enrichment of rare metals along a path of continuous magma differentiation until 75% of the initial melt had crystallized; and iii) a final stage of lithium mineralization during the escape of the water-rich magma due to the overpressures created in response to massive fluid exsolution and the extensional stress in the granite dome structure. The study provides important insights into how lithium-rich pegmatites can be targeted during exploration for pegmatite-hosted resources of lithium.